Physico-Chemical Nature of Salt Affected Soils of Etah and Mainpuri Districts - Singh, K. (Journal of Soil and Water Conservation, 2022)
The present study was performed to investigate (i) physico-chemical nature of salt affected soils of Etah and Mainpuri District of Uttar Pradesh (ii) to find out the degree of correlation between different indices of saline and alkali soils in question. The salt affected soils of both the districts are almost similar in nature, belong mostly to saline-alkali, saline and non-saline-alkali categories too. That is, these soils have been worstly affected by both exchangeable sodium as well as excessive amounts of salt accumulation. The proportion of sodium salts is increasing gradually with the salt deposition. The other important features of soils are high pH, low organic matter and varying hydraulic conductivity at different layers in these soils. The Ca Co, is also invariably present throughout profiles. For improvement of these soils washing out of soluble salts as well as replacement of Exchangeable sodium by calcium would be needed. These problem soils can be easily assessed on the basis of very simple and rapid determination viz. pH, E. C. and G. R. of the salininity and alkalinity status of salt-affected soils of Erah and Mainpuri Districts.